The Kirkpatrick model is utilized in Indonesian language-literature training programs for madrasa teachers in West Java - Faizal Arvianto; Rosita Rahma (Indonesian Journal of Educational Development (IJED), 2026)
An evaluation is required to determine whether a program has achieved its objectives. This process involves collecting data to inform decisions on whether the program should be continued, discontinued, or revised. This article evaluates the Indonesian Language and Literature Learning Evaluation Training program for madrasa teachers in West Java, employing the four levels of the Kirkpatrick evaluation model: reaction, learning, behavior, and results. Primary data were collected from training participants, while secondary data were obtained from evaluation tools created by the participants. Sampling was conducted using saturated and convenience sampling, with data collected via questionnaires, tests, and document analysis. The results indicate a positive reception from participants (reaction), a significant increase in cognitive scores from pre-test to post-test by 37.25% (learning), and a high rate of knowledge transfer, with 82% of participants producing highly appropriate evaluation instruments (results). These findings demonstrate that the training effectively bridged the gap between theoretical knowledge and classroom implementation. Based on these outcomes, the authors provide recommendations for program sustainability, including optimized scheduling, module development, intensive monitoring, and the establishment of periodic evaluation success criteria.